The Reliability Analysis of Sheet Pile Wall Located in Soil with Random Properties Based on CPTu Results - KAWA, Marek; BAGIŃSKA, Irena; WYJADŁOWSKI, Marek (Engineering Transactions, 2017)
The paper deals with reliability analysis of sheet pile wall located in soil with strong spatial variability of strength properties. The purely frictional soil with the strength governed with Mohr-Coulomb criterion has been considered. Spatial variability of friction has been described using random fields theory. Implementation of Local Average Subdivision (LAS) algorithm has been used for generation of individual realizations of the field. Mean and variance as well as fluctuation scale of friction angle has been estimated for assumed exponential correlation model using the results obtained with CPTu testing in natural non-cohesive soil. Using the generated unidirectional field of friction the probabilistic analysis of sheet pile wall has been performed with finite difference method (FLAC). In the final step of the calculation, reliability analysis have been applied. The obtained results prove usefulness of the presented methodology for reliability based design of sheet pile walls.